HOW INTERNET HUMOR IS CHANGING THE ENGLISH LANGUAGE (International Conference on Education, Psychology and Humanities, 2026)
This thesis examines the influence of internet humor on the contemporary English language. The study analyses how memes, viral expressions, social media abbreviations and platform-specific genres reshape vocabulary, syntax, spelling and pragmatic norms. The results demonstrate that internet humor functions as a productive source of linguistic innovation and as a powerful agent of language change in the digital era.
Keywords: Internet humor, memes, English language, language change, digital communication, social media, neologisms, computer-mediated communication, sociolinguistics, viral expressions.